The Position of Wali Al Mal in Islamic Law Structure in Indonesia - Mohamad Saran; Dudang Gojali (Universitas Muhammadiyah Sidoarjo, 2018)
This research was conducted to describe and also analyze the facts regarding guardianship in carrying out their functions and responsibilities as guardians of children who have not yet been in high school. This study uses normative juridical approach, using the statue approach with analytical descriptive method. The results of this study that a guardian for a child has an obligation and responsibility in his care, both in managing the wealth of children under guardianship, education and the survival of children up to adulthood, namely when they are 21 or married. property rights not only include material things, but also include things that are immaterial, as long as this immaterial thing has economic value. According to Islamic law which is the basis of guardianship in stipulating the provisions of guardianship and law, it is always based on the Qur'an remembering how important it is to safeguard property, especially to the assets of orphans.